O PLANO MUNICIPAL DE SANEAMENTO BÁSICO COMO FERRAMENTA DE DESENVOLVIMENTO INSTITUCIONAL EM IJUÍ-RS - Daronco, Giuliano C.; Campos, Tâmela A.; Bernardi, Cândida; Silva, Carlos F. S. C. e.; Pires, Gustavo M. (Salão do Conhecimento, 2013)
Resumo